Causal attributions of mental health problems and depressive symptoms among older Somali refugees in Finland. (April 2017) - Kuittinen, Saija; Mölsä, Mulki; Punamäki, Raija-Leena; Tiilikainen, Marja; Honkasalo, Marja-Liisa
Causal attributions of mental health problems play a crucial role in shaping and differentiating illness experience in different sociocultural and ethnic groups. The aims of this study were (a) to analyze older Somali refugees' causal attributions of mental health problems; (b) to examine the associations between demographic and diagnostic characteristics, proxy indicators of acculturation, and causal attributions; and (c) to analyze the connections between causal attributions and the manifestation of somatic-affective and cognitive depressive symptoms. A sample of 128 Somali refugees aged 50–80 years living in Finland were asked to list the top three causes of mental health problems. Depressive symptoms were analyzed using the Beck Depression Inventory (BDI). The results showed that the most commonly endorsed causal attributions of mental health problems were jinn, jealousy related to polygamous relationships, and various life problems. We identified five attribution categories: (a) somatic, (b) interpersonal, (c) psychological, (d) life experiences, and (e) religious causes. The most common causal attribution categories were life experiences and interpersonal causes of mental health problems. Men tended to attribute mental health problems to somatic and psychological causes, and women to interpersonal and religious causes. Age and proxy indicators of acculturation were not associated with causal attributions. Participants with a psychiatric diagnosis and/or treatment history reported more somatic and psychological attributions than other participants. Finally, those who attributed mental health problems to life experiences (e.g., war) reported marginally fewer cognitive depressive symptoms (e.g., guilt) than those who did not. The results are discussed in relation to biomedical models of mental health, service use, immigration experiences, and culturally relevant patterns of symptom manifestation.